Enhancing Efficiency in Cloud Data Streaming: A Thorough Examination- the entire review - Suhad Sameer; Karim Q. Hussein (Journal of Madenat Alelem University College, 2024)
The ubiquity of cloud computing has brought about a revolutionary change in the data processing landscape. The foundation of real-time data processing, cloud data streaming, has become vital for businesses looking for quick insights and well-informed decision-making. On the other hand, the performance optimisation of cloud data streaming systems presents complex issues that require investigation. This thorough review article explores the complex landscape of improving cloud data streaming performance. It includes basic principles, measures for assessing performance, joint difficulties, sophisticated optimisation techniques, illustrative case studies, platform comparisons, trends to look out for, and recommendations for additional research.